Study of the efficacy of the Portuguese cooperative taxation - Aguiar, Nina; Meira, Deolinda; Raquel, Sandra (REVESCO. Revista de Estudios Cooperativos, 2015)
The Portuguese legal system encompasses a special tax regime for cooperative societies based, like many other legal systems like the Spanish or the Italian systems, on the protection of mutualism as a business organization form with particular social advantages. In order to achieve that goal the cooperative tax regime must be selective; in other words, the legislator must find objective criteria to distinguish cooperatives that deserve tax protection from those that do not. The Portuguese model is based on a main division of cooperatives into two groups according to their activity sector. Both the exemptions and the eligibility requisites are quite different for the two groups. This paper deals with the requirements to be met by cooperatives of both groups in order to be granted tax exemptions, analyzing their adequacy to present conditions. Eligibility criteria take into account: i) operations with third parties and with members; ii) income-generating operations related or unrelated to the specific activity of the cooperative; and iii) the existence of a mainly mutualistic structure of labor relations. This model stems from a 1929 law still in force because of legislative inertia. This paper is based on a survey carried out in 64 cooperatives, aimed at determining whether the described criteria (used for selecting those cooperatives that may benefit from tax exemption) are adequate to the present cooperative reality. As expected, significant shortcomings have been found due to the application of an outdated regime, calling for urgent reform.